Development of a novel sensor for gear teeth wear and damage detection - Sridhar, V; Chana, K (PHM Society, 2021)
Health monitoring of mechanical transmission systems is an important area of research. Mechanical transmission systems, especially gear boxes in aircraft, automobiles, and wind turbines etc. account for many of the maintenance costs due to repairs, replacements and downtime. Gear boxes can experience high level of failure due to varied load conditions and harsh environments. Replacing the gear box is quite an expensive process and has significant downtime. Current gear box monitoring involves mainly measuring vibrations, however vibrations occur when the fault in the gear has already progressed significantly. Gear teeth monitoring lacks sensor technology to successfully detect tooth damage and misalignment. This paper presents a new concept gear teeth damage detection using eddy current sensors fitted on to the teeth of an idler gear at various locations. These sensors detect various faults encountered in a gear such as micro and macro pitting of the tooth surface, contact wear etc. Eddy current sensors are already being used to detect turbomachinery blade vibrations and tip clearance as they are robust and immune to contamination. In the present case, we use an idler gear that incorporates miniature eddy current sensors and state of the art electronics with wireless data transmission to enable the device to operate remotely and in harsh environments. A rotating rig with gears (spur and helical) and oil supply was built to test and validate the sensor by seeding various faults on the tooth surface. The results show that the idler sensor gear was able to detect various faults. The new eddy current sensor idler gear concept will enable health monitoring of the gearbox and ensure timely maintenance and reduction in operation costs.